Drug-related problems and clinical risk factors relationship in hepatic cirrhosis patients - Amelia Lorensia; Widyati .; Aziz Hubeis; Hary Bagijo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Diffusion processes in hepatic cirrhosis is characterized with fibrosis and structural changed. Patients with cirrhosis are at risk to get problems because of the effects of the drugs used have drug-related problems (DRPs), due to changes in heart function that affects many aspects of drug pharmacokinetics. Therefore, treatment of patient with hepatic cirrhosis should consider the drug and dose adjustment so that subsequent problems could be avoided. The research method was prospective and descriptive, with a purposive sampling technique. Patients’s treatment were monitoring and analyzed. Significance of 0000 means that p (0000) <0.05, then the Pearson correlation test results are H1a, ie there was a relationship between the numberof DRPs events by the total number of clinical risk factors of DRPs in patientswith cirrhosis. Therefore from this relationship could be expected to know the possible risk of DRPs in patients. The increasing number of clinical risk factors DRPs in patients with cirrhosis, indicate thatthe patient should receive a more stringent monitoring of the provision of therapy because the risk of experiencing DRPs more.Key words: cirrhosis, drug related problems (DRPs), clinical risk factors of DRPs